Influence of parental attitude in feeding on early caries in preschool age at Kemala Bhayangkari Kindergarten: Pengaruh sikap orang tua dalam pemberian makan terhadap karies dini usia prasekolah di TK Kemala Bhayangkari - Mila Febriany; Eva Novawaty; Patricia Luthfiah Suherman (Makassar Dental Journal PDGI Makassar, 2023)
Caries can cause dental pain that can reduce children's activities and reduce appetite, which in turn can interfere with children's physical growth. Poor parental attitudes can cause anxiety in children and affect the incidence of oral disease because it makes children less likely to maintain oral hygiene or increased sugar consumption, has been shown to cause plaque accumulation which increases the risk of caries. The study aimed to determine the effect of parental attitudes in feeding on the occurrence of early caries in preschool children. This study used an analytic observational method and was included in a cross-sectional research design. The statistical test used was Spearman; on 60 samples. Based on the results of the Spearman correlation test, the p-va-lue of 0.002 is smaller than 0.05 in the control of eating (COE) category. This means that there is an influence of parental at-titudes in feeding on early caries in children. It is concluded that there is an influence of parental attitudes in feeding on early caries in preschool children, namely in the COE category.